Calculus for business, economics, and the social and life sciences - Hoffmann, Laurence D (McGraw-Hill, 2007)
Includes bibliographical references and index; 7 chapters: Functions, graphs and Limints; differentiation: basic concepts; additional applications of the derivatie; exponential and logarithmic functions; intergration; additional topics in tegration; calculus of several variables.